Pengaruh Persepsi Kegunaan, Kemudahan Penggunaan, Risiko terhadap Sikap dan Intensi Perilaku Nasabah dalam Penggunaan Internet Banking di PT. Bank Muamalat Indonesia, Tbk Cabang Jember - Ria Sri Hardiningtyas; Andi Sularso; Bambang Irawan (Jurnal Ekonomi Akuntansi dan Manajemen, 2017)
This study aims to examine the factors that influence customer behavior intention on internet banking services by adopting a conceptual framework Technology Acceptance Model (TAM) developed by Davis in 1989 in PT Bank Muamalat Indonesia, Tbk. Jember Branch. The data collection is done by distributing 200 questionnaires to customers who use internet banking services. Results of the test data showed that the perceived of usefulness, ease of use, and risk significantly affect the attitude of the use of internet banking but the behavioral intention variable significantly influenced only by the perceived ease of use variable. Attitude variable significantly influence behavior intention variable. These results indicate that the behavior intention to use internet banking service foremost influenced by the easiness of the application. A usefull service will not necessarily be used when deemed difficult to operate. The risk factor was not affect the intention of customers to continue using internet banking services. Internet banking services of PT Bank Muamalat Indonesia, Tbk. Jember branch should be more focused on the easiness of the application and the dissemination about how to use this service which in turn can reduce the operational costs of banks in providing banking services. Keywords: Technology Acceptance Model (TAM), internet banking, perceived usefulness, perceived ease of use, perceived risk, attitudes, behavior intention, Structural Equation Model